Determinants of Work Stress: Analysis of Workload and Work Conflict in Private Elementary School Education Personnel in Bogor City - Jumadi, Jumadi; Yusnita, Nancy; Sunaryo, Widodo (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to analyze the determinants of job stress, namely workload and work conflict, among 179 education personnel in private elementary schools in Bogor City, Indonesia, using the Job Demands-Resources (JD-R) model. Employing a quantitative explanatory causal method with a cross-sectional survey design and a multistage random sampling technique, this research investigates the influence of these job demands on perceived stress levels. Data were collected through questionnaires distributed to the selected sample of education personnel. The results of the multiple linear regression analysis revealed that both workload and work conflict simultaneously and partially exert a statistically significant positive effect on job stress. Specifically, higher levels of workload and increased experiences of work conflict were associated with greater reported job stress among the respondents. These findings underscore the critical role of these job demands as key determinants of stress within this specific occupational group. Consequently, the study highlights the importance for school management to address and mitigate excessive workload and sources of work conflict to reduce job stress among their educational personnel. By identifying these primary determinants, this research contributes valuable insights for developing targeted interventions aimed at fostering a healthier and more supportive work environment within private elementary schools.